A multiscale approach for gas hydrates considering structure, growth kinetics, agglomeration, and transportability under multiphase flow conditions - Bassani, Carlos Lange (2021)
Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES)